2014
DOI: 10.1016/j.jagp.2013.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Services Mini-Screen: A Simple Method to Identify Patients and Caregivers in Need of Enhanced Dementia Care Services

Abstract: Objective The National Alzheimer’s Plan calls for targeted health system change to improve outcomes for persons with dementia and their family caregivers. We explored whether dementia-specific service needs and gaps could be predicted from simple information that can be readily acquired in routine medical care settings. Method Primary family caregivers for cognitively impaired older adults (n=215) were asked about current stress, challenging patient behaviors, and prior-year needs and gaps in 16 medical and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 35 publications
0
30
0
1
Order By: Relevance
“…Only in two studies, data regarding the sample recruitment process was poorly reported (Seike et al., 2014; Tatangelo et al., 2018). Moreover, seven quantitative studies adopted instruments developed ad hoc (Borson, Scanlan, Sadak, Lessig, & Vitaliano, 2014; De Cola et al., 2017; Hirakawa, Kuzuya, Enoki, & Uemura, 2011; Killen et al, 2016; Koenig, Steiner, & Pierce, 2011; Ryan et al, 2010; Steiner et al., 2016); four studies used tools not formally or totally evaluated for validity and reliability (Black et al., 2013; Ducharme et al., 2014; Tanner et al., 2015); four studies used both validated and non‐validated tools (Gallagher et al., 2011; Hughes et al., 2014; Rosa et al., 2010; Seike et al., 2014) and three used validated tools (Bakker et al, 2014; Muangpaisan et al., 2010; Zauszniewski, Lekhak, Yolpant, & Morris, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Only in two studies, data regarding the sample recruitment process was poorly reported (Seike et al., 2014; Tatangelo et al., 2018). Moreover, seven quantitative studies adopted instruments developed ad hoc (Borson, Scanlan, Sadak, Lessig, & Vitaliano, 2014; De Cola et al., 2017; Hirakawa, Kuzuya, Enoki, & Uemura, 2011; Killen et al, 2016; Koenig, Steiner, & Pierce, 2011; Ryan et al, 2010; Steiner et al., 2016); four studies used tools not formally or totally evaluated for validity and reliability (Black et al., 2013; Ducharme et al., 2014; Tanner et al., 2015); four studies used both validated and non‐validated tools (Gallagher et al., 2011; Hughes et al., 2014; Rosa et al., 2010; Seike et al., 2014) and three used validated tools (Bakker et al, 2014; Muangpaisan et al., 2010; Zauszniewski, Lekhak, Yolpant, & Morris, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…First, the AA Greater Los Angeles has developed a brief tool . Another useful tool, a “stress thermometer” rating form, can be provided to caregivers as a brief assessment of burden . Finally, the AA has a tool available to assess caregiver understanding of the disease, knowledge of how to get additional information, ability/willingness to provide care, and knowledge of support resources .…”
Section: Discussionmentioning
confidence: 99%
“…The following resources should be incorporated when designing and delivering curricula for care of older adults: 1) ConsultGeri.org is a Hartford Nursing Institute for Geriatric Nursing resource that provides numerous different care protocols through their "Try This: Best Practices in Nursing Care of Older Adults" program. This includes user-friendly step-by-step guides for conducting a cognitive assessment using The Mini-Cog TM [21,22] or Montreal Cognitive Assessment, known as the MOCA. [23] The 2014 Alzheimer's Facts and Figures Report calls for more nurses to be trained in conducting cognitive screening.…”
Section: Educational Resourcesmentioning
confidence: 99%